Summary of studies on Guanacaste’s past - Pizarro Méndez, Yanina (2026)
This article is essentially a historiographical assessment, beginning with a review of fundamental studies on the history of Guanacaste, Costa Rica (emerging since the 1980s), and then focusing entirely on a particular research project and experience developed more recently. The text provides an overview of certain historiographical developments and seeks to highlight the conditioning or influence of different contexts when addressing the region’s key issues (environmental transformations; natural and man-made disasters; conflict and power relations). Similarly, it pays attention to the use and treatment of sources, the working methods employed, as well as the contributions, achievements and goals attained, based on this research experience. All this with the aim of encouraging reflection on how to address current difficulties through scientific research, outreach and university teaching.